2003
DOI: 10.2337/diacare.26.7.2220
|View full text |Cite
|
Sign up to set email alerts
|

Putting Diabetes to the Test

Abstract: A lthough the number of children and youth with type 2 diabetes is increasing, a clear case definition that describes children with type 2 diabetes at presentation remains elusive. Most initial diagnoses are decided on the clinical picture at presentation (1). Characteristics and risk factors have been outlined in several review and clinical articles (2-4). The purpose of this study was to describe the characteristics of youth presenting for an initial visit to the outpatient clinic of a large tertiary childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 6 publications
3
29
1
Order By: Relevance
“…The other important factors affecting HbA 1c level was the level of diabetes knowledge which indicated that people with higher level of knowledge had also higher HbA 1c . This finding is however is different to the finding of other studies (18,19) which found that diabetes knowledge is associated with better glycemic control. The positive correlation found in this current study is, however consistent with the finding of Al-Asani et al (13).…”
Section: Discussioncontrasting
confidence: 99%
“…The other important factors affecting HbA 1c level was the level of diabetes knowledge which indicated that people with higher level of knowledge had also higher HbA 1c . This finding is however is different to the finding of other studies (18,19) which found that diabetes knowledge is associated with better glycemic control. The positive correlation found in this current study is, however consistent with the finding of Al-Asani et al (13).…”
Section: Discussioncontrasting
confidence: 99%
“…Although knowledge by itself does not necessarily lead to improved self-care behaviours or outcomes (Norris et al 2001), an understanding of the disease, its course and treatment and how all these interact are pre-requisites for effective selfcare (Golay et al 2008;Persell et al 2004). Some studies have also demonstrated a positive relationship between disease knowledge and self-care behaviours (Van den Arend et al 2001;Persell et al 2004) and glycaemic control (Colleran, Starr & Burge 2003;Persell et al 2004). This clearly demonstrates a need for improving the basic knowledge about the disease and its treatment.…”
Section: Knowledge About Diabetes and Its Treatmentmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18] Higher diabetes-related knowledge (DRK) has been associated with improved glucose control 11 , lower blood pressure 11 , enhanced quality of life 10,14,19,20 , and improved selfcare behaviors such as dietary adherence 11,12,[21][22][23] , home glucose monitoring 11,12,20,21 , increased exercise 11,21 , and foot inspection 11,21 . Assessment of DRK by the validated Michigan Diabetes Knowledge Test (DKT) 24 may help determine what diabetes education is required, and to monitor knowledge educational progress over time.…”
Section: Introductionmentioning
confidence: 99%